1997
DOI: 10.1086/301633
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the NF2 Tumor-Suppressor Gene in Schwannomatosis

Abstract: Patients with multiple schwannomas without vestibular schwannomas have been postulated to compose a distinct subclass of neurofibromatosis (NF), termed "schwannomatosis." To compare the molecular-genetic basis of schwannomatosis with NF2, we examined the NF2 locus in 20 unrelated schwannomatosis patients and their affected relatives. Tumors from these patients frequently harbored typical truncating mutations of the NF2 gene and loss of heterozygosity of the surrounding region of chromosome 22. Surprisingly, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
123
1
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(133 citation statements)
references
References 29 publications
4
123
1
5
Order By: Relevance
“…The other 5 patients were excluded although they fulfilled the research criteria 17 for schwannomatosis for the following reasons: blood samples of 2 patients under 30 years of age were not available, and 3 patients under 45 years of age had not undergone cranial MR imaging. Of the 65 patients with schwannomatosis, 51 had highquality cranial MR images.…”
Section: Results Patient Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other 5 patients were excluded although they fulfilled the research criteria 17 for schwannomatosis for the following reasons: blood samples of 2 patients under 30 years of age were not available, and 3 patients under 45 years of age had not undergone cranial MR imaging. Of the 65 patients with schwannomatosis, 51 had highquality cranial MR images.…”
Section: Results Patient Groupsmentioning
confidence: 99%
“…Detecting the mutations of the NF2 gene in a single tumor cannot help to differentiate schwannomatosis from NF2, because mutations of the NF2 gene are also common in tumors of patients with schwannomatosis. 17,34 Mutations of the NF2 gene in schwannomatosis are believed to be caused by a "four-hit mechanism;" 14,34 types of mutations in different tumors should be random. Plotkin et al 30 suggested detecting NF2 mutations in 2 or more separate tumors of patients with schwannomatosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the hallmark of schwannomatosis is different somatic variants in multiple tumors from the same patient. 2 Schwannomatosis is a genetic condition, but for poorly understood reasons its occurrence does not follow common inheritance patterns. The majority of cases are sporadic with 15-25% of cases being inherited from an affected parent.…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1990s the suggestion was made that schwannomatosis should be classified as a separate condition [21]. The first clinical diagnos tic criteria were formulated in 1997 by Jacoby et al [12]. Contemporary diagnostic clinical criteria for schwannomatosis were established in 2005 during a meeting under the patronage of the National Neu rofibromatosis Foundation [20].…”
Section: Discussionmentioning
confidence: 99%